2015
DOI: 10.1074/jbc.m114.605816
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Positive Transcription Elongation Factor b (P-TEFb) Activation in Living Cells

Abstract: Background: Positive transcription elongation factor b (P-TEFb) partitions between free (active) P-TEFb and inactive 7SK small nuclear ribonucleoprotein (snRNP) in cells. Results: Bimolecular fluorescence complementation (BiFC) detects interactions between active P-TEFb and its C-terminal domain substrate in vivo. Conclusion: BiFC follows the release of P-TEFb from 7SK snRNP in living cells. Significance: This system is the first to monitor P-TEFb activation in living cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…Additionally, compounds that induce reactivation have recently been found to either induce release of P-TEFb (i.e. PKC agonist PMA, HMBA) (Bernstein and Kappes, 1988; Contreras et al, 2007; Fujinaga et al, 2015; Smith et al, 1992) or function as dual kinase-BET inhibitors targeting BRD4 (i.e. PI3K-mTOR inhibitor PP-242 and the PI3K inhibitor LY294002) (Camarena et al, 2010; Ciceri et al, 2014; Dittmann et al, 2014; Kobayashi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, compounds that induce reactivation have recently been found to either induce release of P-TEFb (i.e. PKC agonist PMA, HMBA) (Bernstein and Kappes, 1988; Contreras et al, 2007; Fujinaga et al, 2015; Smith et al, 1992) or function as dual kinase-BET inhibitors targeting BRD4 (i.e. PI3K-mTOR inhibitor PP-242 and the PI3K inhibitor LY294002) (Camarena et al, 2010; Ciceri et al, 2014; Dittmann et al, 2014; Kobayashi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple positive and negative signals are known to converge on NELF-driven transcriptional pausing. P-TEFb relieves NELF repression through phosphorylation [43] and is itself regulated by cellular stress and signals [44][45][46]. Furthermore, we have shown that NELF interacts with co-repressors including NCoR1-GPS2-HDAC3 at the HIV-1 promoter [47] which may reinforce HIV latency, especially during chronic infection, by facilitating post-translational modifications of histones and chromatin organization.…”
Section: Discussionmentioning
confidence: 99%
“…Previously we demonstrated that most LRAs efficiently release P-TEFb from 7SK snRNP and stimulate CDK9 activity [128]. Other compounds such as HMBA; PKC agonists such as PMA, ingenols, and Bryostatin-1; DNA-damaging agents; and nucleotide analogues including Azacytidine also release P-TEFb [161,162,171,172,178,275]. Recently, we established an assay to monitor P-TEFb-release in live cells based on bimolecular fluorescence complementation (BiFC) [275].…”
Section: Increasing P-tefb Activitymentioning
confidence: 99%
“…Other compounds such as HMBA; PKC agonists such as PMA, ingenols, and Bryostatin-1; DNA-damaging agents; and nucleotide analogues including Azacytidine also release P-TEFb [161,162,171,172,178,275]. Recently, we established an assay to monitor P-TEFb-release in live cells based on bimolecular fluorescence complementation (BiFC) [275]. This Visualization of P-TEFb Activation in Cells (V-PAC) assay quickly tests the ability of compounds of interest to activate P-TEFb by releasing it from 7SK snRNP [275].…”
Section: Increasing P-tefb Activitymentioning
confidence: 99%
See 1 more Smart Citation